Ion covalent organic framework memristive device with vinylidene connection and preparation and application of ion covalent organic framework memristive device

By using substrate-assisted hydrothermal method on the ITO surface, a ionic covalent organic frame film is grown to solve the processing problems caused by material rigidity and high chemical stability, and a memristor with nonvolatile rewritable storage behavior is realized, with bistable and triple-stable behaviors, and good stability is maintained in multiple tests.

CN119630167APending Publication Date: 2025-03-14EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411664302.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing vinylidene-linked ionic covalent organic frame materials have fewer applications in the memristor direction, mainly due to the challenges of subsequent processing processes caused by the rigid structure of the material and the high chemical stability.

Method used

Through substrate-assisted hydrothermal method, a uniformly textured two-dimensional ionic covalent organic frame film was successfully grown on the ITO surface. Two ionic COFs based on vinylidene-linked (COF-EB and COF-ECu3) were designed, and the tri-core copper structure was introduced through redox to optimize the multi-stage conductivity of the material.

Benefits of technology

While maintaining the intrinsic advantages of the material, it is achieved to overcome processing difficulties and prepare a memristor with nonvolatile erasable storage behavior. COF-EB shows bistable behavior, COF-ECu3 shows triple steady-state behavior, and maintain good switching stability in multiple voltage pulse tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630167A_ABST
    Figure CN119630167A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic / polymer neuromorphic information storage, and provides an ion covalent organic framework memristor device with vinylidene connection and preparation and application thereof. Specifically, two construction units (triphenylbenzene and trinuclear copper) with different activities grow a vinyl-bridged ion covalent organic framework film on the surface of ITO through a green hydrothermal method, and the vinyl-bridged ion covalent organic framework film is used as a resistive random access memory. According to the method, a large-area and uniform-texture two-dimensional COF film is successfully grown on the ITO substrate through a green substrate assisted hydrothermal method, and the subsequent film forming processing problem caused by the intrinsic characteristics of vinyl COF is effectively solved; the adopted hydrothermal method opens up a new path for large-scale low-carbon production of the high-crystallinity two-dimensional vinyl ion covalent organic framework material, and has profound significance and value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention, belonging to the field of organic / polymer neuromorphic information storage technology, provides a design and preparation method for hydrothermally synthesized ionic covalent organic framework films. Specifically, two building blocks with different activities (triphenylbenzene and trinuclear copper) are used to grow vinyl-bridged ionic covalent organic framework films on an ITO surface via a green hydrothermal method for resistive memory devices. Background Art

[0002] Driven by the demand for low-power storage and high-density integration, organic memristor technology has demonstrated unique application potential in digital logic circuits and neuromorphic computing. However, improving memristor performance lies in developing suitable two-dimensional active layer thin film materials. While traditional two-dimensional materials, such as black phosphorus, possess electronic properties, their limited stability and electronic control significantly hinder the further application of memristor technology. In recent years, vinyl-bridged two-dimensional ionic covalent organic frameworks (COFs) have garnered widespread attention due to their attractive properties, including well-defined pore structures, flexible molecular design, and π electron delocalization. Vinyl-linked COFs exhibit excellent environmental stability, maintaining excellent crystallinity even in high concentrations of acid or base. Furthermore, the materials are highly designable, allowing the overall framework to be tuned by varying the organic monomers, such as by constructing a DA system or incorporating a redox system, thereby optimizing the material's in-plane charge transport properties. Furthermore, by protonating the COF and introducing ions, the surface charge density can be modulated, allowing ions to migrate under the influence of an electric field, further improving device stability and reliability.

[0003] Despite this, the application of vinylidene-linked ionic covalent organic frameworks in memristor applications is relatively limited, primarily due to the material's rigid structure and high chemical stability, which pose challenges in subsequent processing. Therefore, overcoming these processing challenges while maintaining the material's inherent advantages has become a key issue in current memristor material research. Summary of the Invention

[0004] To address these challenges, we propose a material design and synthesis strategy. Using a substrate-assisted hydrothermal method, two monomers and a catalyst were dissolved in appropriate amounts of water. The indium tin oxide (ITO) was then inverted in a vacuum reaction tube. A three-step freeze-thaw cycle successfully synthesized a uniform two-dimensional ionic COF thin film on the substrate. By tuning the electroactivity of the building blocks, we designed two vinylidene-linked ionic COFs (COF-EB and COF-ECu3). Testing revealed that the fabricated Al / iCOF / ITO devices exhibited stable nonvolatile erasable and rewritable memory. COF-EB exhibited excellent bistability, with turn-on and turn-off voltages of -0.75±0.25V and 2.25±0.25V, respectively. COF-ECu3 exhibited typical tristable behavior, with turn-on voltages of -0.5±0.07V and -0.94±0.11V, respectively, and an off voltage of 2.08±0.28V. By changing the designed monomer from triphenylbenzene to trinuclear copper, the introduction of redox makes it possible to develop the material in terms of multi-level conductive states.

[0005] The first purpose of the present invention is to provide a non-volatile erasable memory with a vinylidene-linked ionic covalent organic framework film as an active layer, that is, a covalent organic framework memory device with non-volatile memory and rewritable properties, and a vinylidene-linked ionic covalent organic framework memory device.

[0006] The second object of the present invention is to provide a green synthesis method of vinylidene-linked ionic covalent organic frameworks, overcoming the traditional toxic organic solvent thermal synthesis through a new green hydrothermal synthesis method.

[0007] The third object of the present invention is to provide a method for preparing a vinylidene-linked ionic covalent organic framework film and using it as a non-volatile erasable and rewritable memory.

[0008] The fourth object of the present invention is to design a novel tri-nuclear copper structure ionic covalent organic framework to realize a memristor with multi-stable behavior.

[0009] The technical solution of the present invention:

[0010] A non-volatile erasable and rewritable memory device with an ionic covalent organic framework thin film material connected by vinylidene groups as an active layer has the following structure from bottom to top:

[0011] 1. Glass substrate;

[0012] 2. Indium tin oxide electrode (ITO);

[0013] 3. iCOF thin film active layer (polymer COF thin film active layer);

[0014] 4. Aluminum electrode.

[0015] Furthermore, the thickness of the iCOF thin film active layer is 150 nm-200 nm.

[0016] Furthermore, the aluminum electrode has a thickness of 100-150 nm.

[0017] The present invention provides a method for preparing a vinylidene ion covalent organic framework thin film device with non-volatile memory and rewritable properties, comprising the following steps (preparing COF-EB):

[0018] 1) Clean the ITO-coated glass plate and dry it;

[0019] 2) Add N-ethyl-2,4,6-trimethylpyridinium bromide (0.01 mmol) into a vacuum reaction tube;

[0020] 3) Add 1,3,5-tris(4-formylphenyl)benzene (0.01 mmol);

[0021] 4) Add 4-dimethylaminopyridine (0.06 mmol);

[0022] 5) Add 1 ml of deionized water and sonicate for 20 minutes to obtain a uniform dispersion;

[0023] 6) Place the pre-cleaned ITO glass plate in the tube (with the ITO side facing down);

[0024] 7) Place the vacuum reaction tube containing the substrate in liquid nitrogen to freeze, then evacuate for 1 minute, seal the tube tightly and thaw, repeating this process three times;

[0025] 8) The obtained vacuum mixed dispersion was placed in an oven at 120°C and heated for 3 days;

[0026] 9) After the reaction mixture cooled to room temperature, the ITO substrate was removed and the film was washed several times with deionized water, ethanol, dichloromethane, and N,N-dimethylformamide;

[0027] 10) Dry the ITO device containing the thin film in a vacuum oven at 50° C. overnight to remove excess solvent.

[0028] 11) Using thermal evaporation method, Al (thickness 150nm, area 0.2×0.2mm 2 ) is plated on the active layer through a mask plate, and finally the device Al / COF-EB / ITO is obtained.

[0029] Preparation method of COF-ECu3 thin film device (same as above);

[0030] 1) Add N-ethyl-2,4,6-trimethylpyridinium bromide (0.01 mmol) into a vacuum reaction tube;

[0031] 2) Add trinuclear copper (0.01 mmol);

[0032] 3) Add 4-dimethylaminopyridine (0.06 mmol);

[0033] 4) Add 1 ml of deionized water and sonicate for 20 minutes to obtain a uniform dispersion;

[0034] 5) Place the pre-cleaned ITO glass plate in the tube (with the ITO side facing down);

[0035] 6) Freeze the vacuum reaction tube containing the substrate in liquid nitrogen, then pump the tube for 1 minute, seal it tightly, and thaw. Repeat this process three times.

[0036] 7) The obtained vacuum mixed dispersion was placed in an oven at 120°C and heated for 3 days;

[0037] 8) After the reaction mixture cooled to room temperature, the ITO substrate was removed and the film was washed several times with deionized water, ethanol, dichloromethane, and N,N-dimethylformamide;

[0038] 9) Dry the ITO device containing the thin film in a vacuum oven at 50° C. overnight to remove excess solvent.

[0039] 10) Using thermal evaporation method, Al (thickness 150nm, area 0.2×0.2mm 2 ) is plated on the active layer through a mask plate, and finally the device Al / COF-ECu3 / ITO is obtained.

[0040] 11) The structural formula of the material in the film provided by the present invention is as follows:

[0041]

[0042] The method for preparing COF powder of the present invention is as follows:

[0043] 1) Synthesis of N-ethyl-2,4,6-trimethylpyridinium bromide (ETMP-Br):

[0044] 2,4,6-Trimethylpyridine (1.25 mL, 10.0 mmol) was added to acetonitrile (50 mL) at room temperature. After stirring at 100°C overnight, the solvent was evaporated to obtain a white solid, which was recrystallized from ethyl acetate to obtain 2.31 g of white crystals with a yield of 85%.

[0045] 2) Synthesis of Trinuclear Copper (Cu3L3)

[0046] Add 1-H-pyrazole-4-carboxaldehyde (0.096 g, 1.0 mmol), copper nitrate trihydrate (0.2 g, 0.83 mmol) into the vacuum reaction tube.

[0047] ), N,N-dimethylformamide (6.7 ml), ethanol (6.7 ml), and deionized water (5 ml). This was followed by sonication for 10 minutes to obtain a uniform dispersion, followed by three freeze-pump-thaw cycles in a 120°C oven for 12 hours. After cooling to room temperature, the reaction mixture was vacuum filtered through a 0.45 μm filter and washed several times with water and ethanol to afford bright yellow needle-shaped crystals in a 75% yield.

[0048] 3) Synthesis of COF-EB powder

[0049] ETMP-Br (0.1-0.2 mmol), Cu3L3 (0.1-0.2 mmol), 4-dimethylaminopyridine (0.6-1.2 mmol), and deionized water (2 ml) were added to a vacuum reaction tube. The mixture was then sonicated for 10 minutes to obtain a uniform dispersion. The mixture was then reacted in a 120°C oven for 72 hours using three freeze-pump-thaw cycles. After cooling to room temperature, the mixture was vacuum filtered through a 0.45 μm filter and washed several times with water, ethanol, dichloromethane, and N,N-dimethylformamide to afford a yellow solid in 82% yield.

[0050] 4) Synthesis of COF-ECu3 powder

[0051] ETMP-Br (0.1-0.2 mmol), Cu3L3 (0.1-0.2 mmol), 4-dimethylaminopyridine (0.6-1.2 mmol), and deionized water (1-2 ml) were added to a vacuum reaction tube. The mixture was then sonicated for 10 minutes to obtain a uniform dispersion. The mixture was then reacted in a 120°C oven for 72 hours using three freeze-pump-thaw cycles. After cooling to room temperature, the mixture was vacuum filtered through a 0.45 μm filter and washed several times with water, ethanol, dichloromethane, and N,N-dimethylformamide to yield a dark red solid in 88% yield.

[0052] The structural formulas of COF-EB and COF-ECu3 are as follows:

[0053]

[0054] The material synthesis route is as follows:

[0055]

[0056]

[0057] The present invention innovatively proposes two vinylidene-linked ionic covalent organic framework (COF) films and applies them as active layers to resistive random access memory. The memory adopts a classic sandwich structure, the bottom electrode adopts an ITO glass plate, and the active layer is composed of a vinylidene ion COF film with excellent crystallinity. Under the condition of applying the same scanning voltage, the COF-EB type device exhibits non-volatile bistable characteristics, while the COF-ECu3 type device exhibits non-volatile tristable characteristics. After 200 voltage pulse tests, the device still maintains good switching stability, providing a new perspective for the design and application of multi-state ion COF devices. In addition, through the large voltage pulse of the device, COF-EB exhibits a period turn-on speed of 154ns, and COF-ECu3 exhibits a device turn-on speed of 105ns, which means that the introduction of Cu3L3 promotes the charge transfer rate of the active layer material. The present invention also proposes a synthetic strategy for material thin films: a green substrate-assisted hydrothermal method successfully grows large, uniform, two-dimensional COF films on an ITO substrate, effectively overcoming the subsequent film processing challenges caused by the intrinsic properties of vinyl COF. Furthermore, the hydrothermal method employed in this invention opens up a new path for the large-scale, low-carbon production of highly crystalline two-dimensional vinyl ionic covalent organic frameworks, which has far-reaching significance and value. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 Diagram of iCOF device preparation.

[0059] Figure 2 Powder X-ray diffraction patterns (PXRD) of COF-EB (a) and COF-ECu3 (b).

[0060] Figure 3 Solid-state NMR carbon spectra of COF-EB (a) and COF-ECu3 (b)

[0061] Figure 4 is the pore size distribution of the two COF powders.

[0062] Figure 5 The current-voltage characteristic curves of the devices Al / COF-EB / ITO and Al / COF-ECu3 / ITO.

[0063] Figure 6 Distribution histograms of the turn-on voltage and turn-off voltage of devices Al / COF-EB / ITO (a) and Al / COF-ECu3 / ITO (b).

[0064] Figure 7 Switching stability of devices Al / COF-EB / ITO (a) and Al / COF-ECu3 / ITO (b).

[0065] Figure 8 Turn-on speed diagrams of devices Al / COF-EB / ITO (a) and Al / COF-ECu3 / ITO (b). DETAILED DESCRIPTION

[0066] The embodiments of the present invention will be described in detail with reference to the following drawings so that the features and advantages of the present invention can be more clearly understood.

[0067] Example 1: Preparation of a vinylene-linked covalent organic framework device:

[0068] 1) The ITO-coated glass substrate (0.5 cm×1.5 cm) was washed with detergent and deionized water, and then washed in ethanol, acetone, and isopropanol for 15 minutes respectively and dried.

[0069] 2) ETMP-Br (0.01 mmol), TFPB (0.01 mmol) or Cu3L3 (0.01 mmol), DMAP (0.06 mmol), and 1 ml of deionized water were placed in a vacuum reaction tube and ultrasonicated for 20 minutes to obtain a uniform dispersion.

[0070] 3) The pre-cleaned ITO was then inverted in a sealed tube and subjected to three cycles of freeze-pump-thaw using liquid nitrogen (freeze the vacuum reaction tube containing the substrate in liquid nitrogen, then evacuate for 1 minute, tighten the sealed tube, and thaw, repeating the operation three times). The final step was to ensure that the bottle was in a vacuum state and to react in a 120°C oven for 3 days.

[0071] 4) After the reactants were cooled to room temperature, the ITO substrate was removed and washed several times with deionized water, ethanol, DCM, and DMF.

[0072] 5) Finally, the ITO device containing the thin film was dried in a vacuum oven at 50° C. for 12 h to obtain a thin film with a thickness of about 200 nm.

[0073] 6) Using thermal evaporation, an Al electrode was deposited on the active layer through a mask to obtain a device Al / COF-EB / ITO or Al / COF-ECu3 / ITO. (The Al electrode thickness was 150 nm and the area was 0.2 × 0.2 mm 2 )

[0074] Example 2: The material preparation method of the present invention is as follows:

[0075] 1) Synthesis of N-ethyl-2,4,6-trimethylpyridinium bromide (ETMP-Br):

[0076] 2,4,6-Trimethylpyridine (1.25 mL, 10.0 mmol) was added to acetonitrile (50 mL) at room temperature. After stirring at 100°C overnight, the solvent was evaporated to obtain a white solid, which was recrystallized from ethyl acetate to obtain 2.31 g of white crystals with a yield of 85%.

[0077] 2) Synthesis of Trinuclear Copper (Cu3L3)

[0078] Add 1-H-pyrazole-4-carboxaldehyde (0.096 g, 1.0 mmol), copper nitrate trihydrate (0.2 g, 0.83 mmol) into the vacuum reaction tube.

[0079] ), N,N-dimethylformamide (6.7 ml), ethanol (6.7 ml), and deionized water (5 ml). This was followed by sonication for 10 minutes to obtain a uniform dispersion, followed by three freeze-pump-thaw cycles in a 120°C oven for 12 hours. After cooling to room temperature, the reaction mixture was vacuum filtered through a 0.45 μm filter and washed several times with water and ethanol to afford bright yellow needle-shaped crystals in a 75% yield.

[0080] Example 3: Synthesis of COF-EB powder

[0081] ETMP-Br (0.2 mmol), TFPB (0.2 mmol), 4-dimethylaminopyridine (1.0 mmol), and deionized water (2 ml) were added to a vacuum reaction tube. The mixture was then sonicated for 10 minutes to obtain a uniform dispersion. The mixture was then reacted in a 120°C oven for 72 hours using three freeze-pump-thaw cycles. After cooling to room temperature, the mixture was vacuum filtered through a 0.45 μm filter and washed several times with water, ethanol, dichloromethane, and N,N-dimethylformamide to afford a yellow solid in 82% yield.

[0082] Example 4: Synthesis of COF-ECu3 powder

[0083] ETMP-Br (0.2 mmol), Cu3L3 (0.2 mmol), 4-dimethylaminopyridine (1.0 mmol), and deionized water (2 ml) were added to a vacuum reaction tube. The mixture was then sonicated for 10 minutes to obtain a uniform dispersion. The mixture was then reacted in a 120°C oven for 72 hours using three freeze-pump-thaw cycles. After cooling to room temperature, the mixture was vacuum filtered through a 0.45 μm filter and washed several times with water, ethanol, dichloromethane, and N,N-dimethylformamide to yield a dark red solid in 88% yield.

[0084] The structural formulas of COF-EB and COF-ECu3 are as follows:

[0085]

[0086] The material synthesis route is as follows:

[0087]

[0088]

[0089] Effect implementation: 1

[0090] like Figure 2 Both COF-EB and COF-ECu3 exhibit high crystallinity. Materials Studio simulations show that both materials closely match the typical AA stacking model. 2θ values ​​of approximately 5.7° and 9.2° correspond to the (100) and (110) crystal planes, respectively.

[0091] Effect Example 2

[0092] like Figure 3 The chemical shifts at 20 ppm and 50 ppm are the carbon signals of the pendant alkyl chains of COF-EB and COF-ECu3, and the chemical shift at around 130 ppm is the carbon signal peak of the vinyl group.

[0093] like Figure 4 The pore size of COF-EB is 1.61nm, and the pore size of COF-ECu3 is 1.58nm. Both materials match the pore size of the theoretical model well.

[0094] like Figure 5 ,Al / COF-EB / ITO exhibits nonvolatile bistability behavior, and Al / COF-ECu3 / ITO exhibits nonvolatile tristable behavior.

[0095] Effect Example 4

[0096] like Figure 6 The average turn-on voltage of the device Al / COF-EB / ITO is -0.75V, and the average turn-off voltage is 2.25V; the average turn-on voltage of the device Al / COF-ECu3 / ITO is -0.5V and -0.94V, and the average turn-off voltage is 2.08V.

[0097] Effect Example 5

[0098] like Figure 7 , both devices showed good switching stability under 200 voltage pulses.

[0099] Effect Example 6

[0100] like Figure 8Under a large voltage pulse of 3V, the turn-on speed of Al / COF-EB / ITO is 154ns; the turn-on speed of Al / COF-ECu3 / ITO is 105ns.

[0101] The above-described preparation steps, effect examples, and accompanying data are preferred embodiments of the present invention. Other embodiments within the scope of protection can also achieve the above-mentioned beneficial effects, and will not be described in detail here. It should be noted that those skilled in the art can make several improvements and modifications without departing from the concept of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An ionic covalent organic framework memristor device with vinylene linkages, characterized in that: The device structure from bottom to top is: (1) Glass substrate; (2) Indium tin oxide electrode ITO; (3) Polymer COF film active layer; (4) Aluminum electrode.

2. The ionic covalent organic framework memristor device with vinylene linkage according to claim 1, characterized in that: The structure of the COF film in the polymer film active layer is shown in the following formula:

3. The ionic covalent organic framework memristor device with vinylene linkage according to claim 1, characterized in that: The thickness of the polymer COF film active layer is 150 nm-200 nm.

4. The ionic covalent organic framework memristor device with vinylene linkage according to claim 1, characterized in that: The aluminum electrode has a thickness of 100-150 nm.

5. The ionic covalent organic framework memristor device with vinylene linkage according to claim 2, characterized in that: The COF film in the polymer film active layer is prepared by the following steps: 1) Synthesis of N-ethyl-2,4,6-trimethylpyridinium bromide ETMP-Br: 2) Synthesis of Trinuclear Copper Cu3L3: 3) Synthesis of COF-ECu3: Add ETMP-Br 0.1-0.2mmol, Cu3L3 0.1-0.2mmol, 4-dimethylaminopyridine 0.6-1.2mmol, and 2ml of deionized water into a vacuum reaction tube; then perform ultrasonic treatment, and then perform freeze-pump-thaw cycle operation three times in a 120°C oven to react for 72h; after cooling the reactant to room temperature, filter and wash to obtain a dark red solid; or, Replace the steps 2) and 3) with the following step 4): 4) Synthesis of COF-EB Add ETMP-Br 0.1-0.2 mmol, TFPB 0.1-0.2 mmol, 4-dimethylaminopyridine 0.6-1.2 mmol, and deionized water 1-2 ml into a vacuum reaction tube; perform ultrasonic treatment, and then perform freeze-pump-thaw cycle operation three times in a 120° C. oven to react for 72 h; after cooling the reactant to room temperature, filter and wash to obtain a yellow solid.

6. A method for preparing an ionic covalent organic framework memristor device having vinylidene linkages according to any one of claims 1 to 4, characterized in that: The steps include: 1) Clean the ITO-coated glass plate and dry it; 2) adding N-ethyl-2,4,6-trimethylpyridinium bromide into a vacuum reaction tube; 3) adding 1,3,5-tri(4-formylphenyl)benzene or trinuclear copper; 4) adding 4-dimethylaminopyridine; 5) adding deionized water and ultrasonically treating for 20 minutes to obtain a uniform dispersion; 6) Place the pre-cleaned ITO glass plate in the tube; 7) Place the vacuum reaction tube containing the substrate in liquid nitrogen for freezing, then evacuate for 1 minute, and finally tighten the tube seal and thaw, repeating the operation 3 times; 8) The obtained vacuum mixed dispersion was placed in an oven at 120° C. and heated for 3 days; 9) After the reaction mixture cooled to room temperature, the ITO substrate was taken out and the film was treated with deionized water, ethanol, dichloromethane, Wash several times with N,N-dimethylformamide; 10) Dry the ITO device containing the thin film in a vacuum oven at 50° C. overnight to remove excess solvent. 11) Using a thermal evaporation method, Al is plated on the active layer through a mask, and finally a device Al / COF-EB / ITO or Al / COF-ECu3 / ITO is obtained.

7. Use of the ionic covalent organic framework memristor device with vinylene linkages as claimed in any one of claims 1 to 4 in information storage.

Citation Information

Cited By

  • Method for preparing covalent organic framework material based on aqueous-phase electron transfer complex

    CN120157816A